THEME AND THE THEMATIC CONCEPT OF HOPE IN DOSTOEVSKY'S «CRIME AND PUNISHMENT» (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-120-128One of the most important themes of Dostoevsky's novel «Crime and Punishment» connected with the hope for the revival of the criminal's soul is considered. It is concluded that the concept «hope», acquiring religious and philosophical connotations, performs the function of the thematic concept in the novel, embodying the individual-author's features.Key words: theme, thematic concept, hope, Dostoevsky, "Crime and Punishment"